2016
DOI: 10.1016/j.healun.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyloxalylglycine treatment of brain-dead donor rats improves both donor and graft left ventricular function after heart transplantation

Abstract: Objective: The hypoxia inducible factor (HIF)-1 pathway signalling has a protective effect against ischemia/reperfusion injury. The prolyl-hydroxylase inhibitor Dimethyloxalylglycine (DMOG) activates the HIF-1 pathway by stabilizing HIF-1Į. In a rat model of brain death (BD)-associated donor heart dysfunction we tested the hypothesis that a pre-treatment of brain-dead donors with DMOG results in a better graft heart condition. Additionally, compared to brain-dead group, DMOG treatment moderated the proapoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…Bernhardt and coworkers (12) have demonstrated that donor pretreated with a PHD inhibitor (FG-4497) could significantly improve graft function and survival in an allogeneic rodent model of renal transplantation via up-regulation of HIF-1a and its target genes. In a rat model of brain death (BD)-associated donor heart dysfunction, Heged} us et al (10) demonstrated that pretreatment with the PHD inhibitor DMOG resulted in improved early recovery of graft left ventricular function after heart transplantation, supported the hypothesis that activation of HIF-1a and its target genes has a protective role against BD-associated cardiac dysfunction. In addition, Amador et al (31) evaluated the clinical application of ischemic preconditioning (IPC) in deceased donor liver transplantation, the authors demonstrated improved hepatic enzyme levels and reduced reoperation rate in the IPC group with associated activation of the HIF-1 pathway.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bernhardt and coworkers (12) have demonstrated that donor pretreated with a PHD inhibitor (FG-4497) could significantly improve graft function and survival in an allogeneic rodent model of renal transplantation via up-regulation of HIF-1a and its target genes. In a rat model of brain death (BD)-associated donor heart dysfunction, Heged} us et al (10) demonstrated that pretreatment with the PHD inhibitor DMOG resulted in improved early recovery of graft left ventricular function after heart transplantation, supported the hypothesis that activation of HIF-1a and its target genes has a protective role against BD-associated cardiac dysfunction. In addition, Amador et al (31) evaluated the clinical application of ischemic preconditioning (IPC) in deceased donor liver transplantation, the authors demonstrated improved hepatic enzyme levels and reduced reoperation rate in the IPC group with associated activation of the HIF-1 pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Preconditional activation of HIF-1 by a HIF-agonist (EDHB) significantly decreases liver ischemia/reperfusion (I/R) injury through decreased mitochondrial depolarization and prevention of mitochondrial injury (8). The pharmaceutical activation of HIF-1 with the use of synthetic HIF agonists also results in early recovery of graft function in renal, heart and aortic allograft transplantation (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Although most in vivo preclinical studies investigating the effects of PDE5 inhibitors were performed in experimental models of myocardial IR, a limited number of studies have been conducted in an in vivo model of global IR injury. In our laboratory, the effects of vardenafil on global IR injury were investigated using our well-established rat model of heterotopic heart transplantation (Szabo et al, 2002;Loganathan et al, 2015;Hegedus et al, 2016). Our results show that a preconditioning of donor rats with vardenafil (10 μg·kg À1 , i.v.…”
Section: Global Myocardial Ischaemia/reperfusion Injurymentioning
confidence: 88%
“…The experimental model was described elsewhere (18)(19)(20). The experimental model was described elsewhere (18)(19)(20).…”
Section: Model Of Heterotopic Heart Transplantationmentioning
confidence: 99%
“…Based on published in vitro and in vivo findings, we hypothesized that the treatment of BDD with NOD improves both donor and graft left-ventricular (LV) function in our well-established rat model of heterotopic heart transplantation (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%